1999
DOI: 10.1038/sj.gt.3300980
|View full text |Cite
|
Sign up to set email alerts
|

Efficient infection of mature skeletal muscle with herpes simplex virus vectors by using dextran sulfate as a co-receptor

Abstract: The use of herpes simplex virus (HSV) vectors for gene chondroitin ABC lyase, HSV infection was restored, which delivery to skeletal muscle is hampered by a maturationsuggests that virus secondary receptors were present but dependent loss of muscle fiber infectivity. Previous studies not readily accessible to the virus in the intact myofiber. of HSV type 1 (HSV-1) infection in the rodent show that Surprisingly, we also found that HSV-1 infectivity could be the loss of infectivity may be due, at least in part, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…It has been reported that the synthesis of heparan sulfate proteoglycan is down-regulated during murine skeletal muscle maturation, and this has been proposed to be responsible for the loss of HSV infectivity [29] (heparan sulfate acts as a co-receptor for attachment of HSV to cells). Based on this report, we propose the hypothesis that due to low levels of heparan sulfate proteoglycan in muscle, cationic polymers improve the transduction by facilitating the primary interaction between virus and the muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the synthesis of heparan sulfate proteoglycan is down-regulated during murine skeletal muscle maturation, and this has been proposed to be responsible for the loss of HSV infectivity [29] (heparan sulfate acts as a co-receptor for attachment of HSV to cells). Based on this report, we propose the hypothesis that due to low levels of heparan sulfate proteoglycan in muscle, cationic polymers improve the transduction by facilitating the primary interaction between virus and the muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of DS preincubation presents a technique to potently enhance PTD delivery of biologically relevant cargoes to poorly transducible, GAG-low cell lines and primary cells for their manipulation in vitro and ex vivo. Since primary tissues, such as hematopoietic stem cells and differentiated muscle tissue, are known to have down-regulated GAG surface expression, DS might be used to enhance ex vivo protein transduction of these cell types (63,64). Furthermore, the widespread presence of short, arginine/lysine-rich stretches of residues within proteins opens up the possibility that, with or without DS treatment, such proteins may be capable of receptorless entry into cells without the need for modification of their primary sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the virus binding site on the 1 head receptor may be proximal to the cell surface or otherwise sterically inaccessible to soluble virus. In this scenario, virus binding to sialic acid may serve to insert the 1 head into the glycocalyx to permit interaction between this receptor and 1 (63,64). Finally, 1-sialic acid interactions may induce a conformational change in 1 that places the head RBD in a state that displays higher affinity for its receptor, in a mechanism analogous to CD4-induced conformational changes that expose chemokine receptor-binding residues on HIV gp120 (4 -6), although a 1 conformational change alone is not sufficient to enhance attachment, since incubation with SLL inhibits rather than enhances SAϩ binding.…”
Section: Fig 6 Kinetics Of Attachment Of Sa؊ and Sa؉ To Hela Cellsmentioning
confidence: 99%